(3GdCUhd hGdCYQGa GdehMOI ddEYJeGOGJ GdeSJfOjIs - (3LeGd jhSa(B, (3YHO GdfHjs ((3YeGf(B:s (3eQcR GdcJGH GdCcGOjej(B,s, 2013)
(3JYQja GdEYJeGO GdeSJfOj(B- (3CWQGa GdEYJeGO GdeSJfOj(B- (3OhQ heSDhdjI GdCWQGa(B- (3CfhGY GdEYJeGO GdeSJfOj(B- (3YfGUQ GdEYJeGO GdeSJfOj(B- (3GdTQhW GdhGLH JhGaQgG YfO aJM GdEYJeGO GdeSJfOj(B- (3HjGfGJ WdH aJM GdEYJeGO GdeSJfOj(B- (3eQGMd aJM GdEYJeGO hahGFOg(B- (3ELQGAGJ aJM GdEYJeGOGJ GdeSJfOjI aj MGdGJ GdESJjQGO(B- (3GdJahjV HGdJZWjI ebGHd GdEYJeGOGJ GdeSJfOjI(B- (3GdeSJfOGJ GdeWdhHI aj GdYedjI GdJLGQjI(B- (3HhGdU GdEYJeGOGJ GdeSJfOjI GdhGQOI(B- (3ELQGAGJ JSOjO hJSdje HhGdU GdEYJeGOGJ GdeSJfOjI GdhGQOI(B- (3WQb GdJSdje aj GdJLGQI GdNGQLjI(B- (3Cge GdNdGaGJ GdTGFYI aj GdeSJfOGJ GdebOeI Ydi GdEYJeGO(B- (3GdJNdjU Ydi GdHVGFY bHd hUhd GdeSJfOGJ(B- (3GdHhfO hGdefWbI GdMQI(B- (3EdZGA GdEYJeGO GdeSJfOj(B- (3JYOjd GdEYJeGO GdeSJfOj(B- (3GdCUhd hGdCYQGa GdehMOI ddEYJeGOGJ GdeSJfOjI(B- (3fUGFM hEQTGOGJs
Keywords: (3GdEYJeGOGJ GdeSJfOjIs